LITERATURE REVIEW : THE INFLUENCE OF COMPENSATION, JOB SATISFACTION, WORK MOTIVATION, JOB STRESS AND WORKLOAD ON THE PERFORMANCE OF MAXIM ONLINE DRIVER EMPLOYEES IN BEKASI CITY - Elena Syafa Chamilla (Draf Solusi Indonesia, 2023)
This research focuses on a literature review thatinfluences the performance of online drivers in thecity of Bekasi. Some of the variables that are targetedare compensation, job satisfaction, work motivation,job stress and workload. This research uses aquantitative approach to answer research results inaccordance with the research objectives. Thepopulation in this study is not known with certaintyso the minimum sample uses Hair's approach. et al.This research literature is new in that this researchmodel has never been conducted before. Thisresearch also focuses on online drivers and wasconducted in the city of Bekasi.